173k views
1 vote
If f(x)=-x and f(-3), then the result is

User Pauli
by
5.3k points

1 Answer

2 votes

Answer:

f(-3) = 3

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Explanation:

Step 1: Define

f(x) = -x

f(-3) is x = -3

Step 2: Evaluate

  1. Substitute in x: f(-3) = -(-3)
  2. Multiply: f(-3) = 3
User Shekhar G H
by
5.1k points